2023
DOI: 10.1039/d3ee01317k
|View full text |Cite
|
Sign up to set email alerts
|

A facile synthetic approach based on thieno[3,4-c]pyrrole-4,6-dione to construct polymer donors for highly efficient organic solar cells

et al.

Abstract: To realize the application of organic solar cells (OSCs), an emphasis must be placed on reducing material cost, which is one of the golden triangle elements. One key strategy to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 78 publications
0
10
0
Order By: Relevance
“…1 (extracted from Supplementary Table 1 ). Meanwhile, the spectrogram features of P A s with various M w s have obvious differences in solutions 14 , 48 – 51 , which are very suitable for signal tracking and comparative analysis. As exhibited in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…1 (extracted from Supplementary Table 1 ). Meanwhile, the spectrogram features of P A s with various M w s have obvious differences in solutions 14 , 48 – 51 , which are very suitable for signal tracking and comparative analysis. As exhibited in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A PCE of 18.57 % and 19.54 % were achieved for PBTz-F : L8-BO and PBTz-F : PM6 : L8-BO based devices. Min et al synthesized two thieno[3,4c]pyrrole-4,6dione-based polymer donors PTTB-H and PTTB-F. [152] PTTB-F exhibited low energy level and stronger aggregation properties. The OSCs based on PTTB-F : L8-BO exhibited a higher PCE of 18.06 % than that of PTTB-H-based devices due to the reduced non-geminate recombination, improved charge transport, and optimized phase morphology.…”
Section: Fluorinated Benzodithiophenementioning
confidence: 99%
“…In 2023, Min et al reported a synthetic route of DT-TPD through a two-step reaction in a yield of 31 %. [77] The key ring forming reaction was conducted by heating the mixture of 4-alkylthiophene-2-carbaldehyde, S8, 1-methylpyrrolidine-2,5-dione, 2-aminobenzimidazole, NH 4 I, K 2 CO 3 , N-methyl-2-pyrrolidone and H 2 O in 140 °C for 48 hours, yielding DT-TPD (Synthetic route 4).…”
Section: Imide-functionalized Building Unitsmentioning
confidence: 99%
“…designed a TPD-based polymer donor PTTB-F, which showed an decent PCE of 18.06 % in binary OSCs by blending with L8-BO. [77] By employing thieno[3,2-b]thiophene as the π-bridge, Liang et al synthesized TPD-based polymers PBDTT-6ttTPD and PMOT16. [47] By blending with IDIC, the PMOT16-based OSCs exhibited a PCE of 10.04 %.…”
Section: Imide-functionalized Building Unitsmentioning
confidence: 99%